Material Ways of Looking: A Methodological Proposal for Visual and Material Culture Studies - Beck, Lauren (Material Culture Review / Revue de la culture matérielle)

(untitled) (Cape Breton University Press, 2023)
A problem facing art historians and scholars of visual and material culture studies is the white patriarchy that undergirds most visual culture produced in the western world, at least until recent times: whether paintings, book illustration, sculpture, advertising, or the environments that nourish and house these creations, both the producer and the intended viewer for the most part came from one demographic category. Building upon the concept of affordance, this essay questions object-human interactions to propose methodological approaches to visual culture that privilege the inclusion of otherwise siloed or marginalized people (women and people of colour, but also non-western people). By centering on the object represented in or through an image, this essay explores ways of detecting marginalized presence so to foment a more inclusive visual culture while formulating new types of questions that can be asked of our visualized world.